ANALISIS ATAS PEMBACAAN MUHAMMED ARKOUN TERHADAP TURASH-TURASH ISLAM - ainol yaqin (Program Studi Hukum Keluarga Islam, 2019)
The existence of renewal in Islamic religious thought is a necessity because there are new different challenges and problems in each era. Islam as a religion of rahmat lil’ālamīn (a mercy to all creation) advocates and asks Muslims to optimize their logical reasoning in responding to every phenomenon. The existence of Arkoun as a contemporary Muslim thinker makes serious effort in reading, studying and investigating Islamic turath (heritage) with all his teachings in order to deconstruct then reconstruct the epistemology of Islam so that he can move forward in the current era. Arkoun's thought was very intent to dismantle the standard and well-established understandings among Muslims and also dared to counteract “the big waves” in revising and rearranging Islamic scientific construction. For Arkoun, all kinds of knowledge, as well as Islamic religious sciences are linked to the historicity that surrounds them, it cannot be denied that those are a product of history. Therefore, his scientific epistemology is also the product of history and the results of the reasoning creativity of those who lived in a certain era. He proclaims to understand, to examine, to study, to examine and to criticize Islamic religious thought (al-afkār al-dīniyah al-islāmiyah) which is summarized in a number of turath (heritage) using various methods and findings of humaniora (humanistic studies) and social sciences developed since the 19th century, its development was even faster in the 20thcentury.